A visualization and quantification method to evaluate the water-absorbing characteristics of rice. (30th November 2020) - Hu, Zhanqiang; Yang, Hua; Chaima, Mamoun; Fang, Changyun; Lu, Lin; Hu, Xianqiao; Du, Bai; Zhu, Zhiwei; Huang, Jianying
Highlights: A new method was developed to evaluate water-absorbing characteristics of rice. The water-absorbing characteristics of each rice grain could be analyzed. The water-absorbing characteristics had positive correlation with expansion. The appearance of cracks accelerated the absorption of water. Different factors had significant effect on the water-absorbing characteristics. Abstract: A visualization and quantification image analysis method is developed to evaluate the water-absorbing characteristics of rice. A projected image of soaked rice was obtained by a scanner in real time, the expansion ratio of the soaked rice in the projected image was calculated with computer software, and the change in the internal structure was analyzed. The results showed that water absorption had a positive correlation with expansion and the cracks occurred in the internal structure of rice could accelerate the water absorption. The maximum expansion ratio of Japonica rice gradually increased with increased milling time, but that of Japonica glutinous rice was not significantly different ( P  > 0.05). A high soaking temperature shortened the time to reach the maximum expansion ratio and resulted in a lower expansion ratio in the Indica and Indica glutinous rice but had no significant effect ( P  > 0.05) in the Japonica and Japonica glutinous rice.